Influence of visual information on pedestrian actions on laterally oscillating structures – experimental study using virtual reality environments. (2017) - Bocian, Mateusz; Macdonald, John H.G.; Burn, Jeremy F.
Abstract: A new line of inquiry into the causes of lateral instability of structures due to actions of walking pedestrians has been opened recently thanks to the fusion of structural dynamics, biomechanics and experimental psychology. This has been achieved by means of a novel experimental setup. The setup consists of an instrumented treadmill, supported by a shaking table providing lateral motion, a motion capture system for monitoring kinematics of walkers, a treadmill speed feedback control mechanism for automatic adjustment of the treadmill speed to that of the walker and immersive virtual reality implemented to provide similarity of the visual environment with real life experience. It has been previously observed that the visual environment can influence pedestrian behaviour and the resulting ground reaction forces. Statistically significant differences between gait parameters and self-excited forces, critical for structural stability, have been measured during tests in which the visual environment was either that of a laboratory, containing an abundance of stationary visual reference cues, or virtual reality representative of walking on a footbridge. This highlighted the importance of providing visual information representative of real life experience. Another opportunity presented by the experimental setup is explored in this study in that it allows the influence of differently structured visual environments to be tested. To this end, two types of visual scenarios are implemented in virtual reality, differentiated by the amount of visual information available to the walker. It is shown that the visual information can indeed alter pedestrian behaviour and that reducing the amount of visual information can have a detrimental effect for structural stability. This raises a question whether a number of design recommendations proposed in recent years, calibrated based on data from laboratory-based investigations neglecting the influence of visual information on pedestrian behaviour, should be reconsidered and updated.